Pengembangan Media Pembelajaran Berbasis Augmented Reality Pada Mata Pelajaran IPA Materi Struktur dan Fungsi Jaringan Pada Tumbuhan di SMP - dheo fajri kosara; abna hidayati (Universitas Negeri Padang, 2023)
The right learning media with technological developments has an effect on an effective and efficient learning process. Learning media using augmented reality is one solution to this problem. Utilization of learning media using augmented reality technology is useful in improving the learning process and student interest because students are required to think for real without having to bring in practical tools directly. This is the background of this research so as to develop learning media using augmented reality technology to be one solution to increase the interest of students in the learning process This type of research is research and development Research and Development (R&D) using the ADDIE development model. The stages in the development of this development model are: Analysis (Analysis), Design (Design, Implementation), Evaluation (Evaluate). The results of this research and development are augmented reality-based learning media equipped with AR Book as a support. The research sample for product validity, it was carried out by 3 people, namely 2 media validators and 1 material validator, and for the effectiveness test there were 15 students of class VIII SMP Muhammadiyah 5 Padang. Based on the results of the assessment of the research and development of augmented reality-based learning media, it can be concluded that the assessments of two media experts are categorized as